2015
DOI: 10.1124/dmd.115.063412
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Assessment of a New CYP2C9 Allelic Variant CYP2C9*59

Abstract: CYP2C9, one of the most important drug-metabolizing enzymes, is responsible for metabolizing approximately 15% of clinically important drugs, including warfarin, diclofenac, and losartan. Similar to other CYP members, human CYP2C9 exhibits marked genetic polymorphisms among individuals of different ethnicities. In this study, a novel missense mutation (1300A>T) was identified in a warfarin-sensitive patient after a genetic screen of three candidate genes related to high variability in response to warfarin dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Continued allele to *60 variants in insect cells and comprehensively analyzed the kinetic parameters for each of the variant enzymes in the metabolism of losartan, glimepiride, tolbutamide, and diclofenac. [48][49][50][51][52][53] They observed that it was difficult to analyze warfarin metabolism using insect cells. It was therefore indicated that mammalian cells have to be used in expressing CYP2C9*1 to *60 variants to analyze the metabolism of warfarin.…”
Section: Cyp2c9mentioning
confidence: 99%
“…Continued allele to *60 variants in insect cells and comprehensively analyzed the kinetic parameters for each of the variant enzymes in the metabolism of losartan, glimepiride, tolbutamide, and diclofenac. [48][49][50][51][52][53] They observed that it was difficult to analyze warfarin metabolism using insect cells. It was therefore indicated that mammalian cells have to be used in expressing CYP2C9*1 to *60 variants to analyze the metabolism of warfarin.…”
Section: Cyp2c9mentioning
confidence: 99%
“…In our previous studies, results of in vitro and in vivo experiments showed that vonoprazan inhibited CYP3A4, CYP2C9, CYP2D6, and CYP2B6 in vitro and in vivo. 16 It has been previously established that metabolism of VEN is dominated by CYP2D6 and it is transformed into the active metabolite ODV in the liver, [17][18][19] In addition, CYP3A4/5 also participate partially in the metabolism of VEN. 20 Therefore, VEN is susceptible to CYP450mediated DDI, especially through the CYP2D6 metabolic pathway.…”
mentioning
confidence: 99%
“…Some studies on tolbutamide and carvedilol metabolism have shown that compared with the wild-type CYP2C9*1, the CYP2C9*11 (R335W) allele is linked to a decrease in enzyme activity. 28,29 However, in some other studies, it has been noted that CYP2C9*11 may have little to do with the dosage requirements of warfarin, and that it shows a significant increase in the enzyme activity of bosentan metabolism. 43,44 In this study, the catalytic activity of the CYP2C9*11 allele on sildenafil was not significantly different from that of the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…9,24,25 In a recent study, Dai et al sequenced all nine exons of CYP2C9 in 2127 26 In subsequent studies, Luo et al further analyzed the CYP2C9 nine exons in previous 2127 healthy Chinese people and found three novel mutation positions that could result in amino acid variation, which have been named CYP2C9*58 (P337T), CYP2C9*59 (I434F) and CYP2C9*60 (L467P). [27][28][29] CYP3A4 is another important and abundantly expressed CYP450 drug-metabolizing enzyme, which belongs to the human CYP3A subfamily and constitutes ~30% of the total CYPs in human liver. 30 It is in charge of clearing approximately half of clinical drugs that experience phase I metabolic reaction, such as anticancer drugs (tamoxifen), Hypnotics (zolpidem), antibiotics (erythrocin), Hormone Drugs (prednisolone), anticonvulsants (carbamazepine), opioids (fentanyl), calcium channel blockers (nifedipine), antihistamines (loratadine) and so forth.…”
Section: Introductionmentioning
confidence: 99%